Types, Degree and Causes of Hearing Loss in Madrasah Children - Saif Ul Malook; Muhammad Sikander Ghayas Khan; Farzana Mazhar; Malik Muhammad Qasim; Mushtaq, Faiza; Muhammad Shazaib Khan; Asma Sani; Muhammad Safdar Abbas; Muhammad Naeem Mazhar (Journal of Health, Wellness and Community Research, 2025)
Background: Hearing loss is a frequently underdiagnosed condition among children attending Madrasahs, with significant consequences for academic progress and psychosocial development. Conductive hearing loss predominates in such settings, often resulting from preventable factors such as trauma and ear infections, yet systematic data on prevalence and etiology remain scarce in low-resource contexts. Objective: To determine the types, degrees, and causes of hearing loss in male Madrasah students aged 5–16 years in Dera Ghazi Khan, Pakistan, and to identify clinically significant associations between etiological factors and severity of impairment. Methods: In this cross-sectional observational study, 100 male students were selected via purposive sampling from a Madrasah. Each participant underwent otoscopic examination and pure tone audiometry following standard protocols. Hearing loss was categorized by type and severity; etiological data were collected through clinical assessment and structured parent interviews. Statistical analyses included descriptive and inferential statistics, with odds ratios and confidence intervals used to assess associations between trauma and severity of loss. Results: Conductive hearing loss was present in 63% of students, with moderate loss identified in 35%. Trauma accounted for 34.3% of hearing loss cases and was strongly associated with moderate severity (OR: 2.98, 95% CI: 1.32–6.71, p=0.008). Otitis externa (25.4%) and otitis media (11.9%) were also prominent causes. No significant association was found between hearing loss prevalence and duration of Madrasah study. Conclusion: Conductive hearing loss is highly prevalent among Madrasah students, with trauma and preventable infections as leading contributors. Implementation of routine auditory screening, injury prevention, and health education in Madrasahs is warranted to mitigate the burden of hearing impairment.